STUDI TENTANG PENILAIAN HASIL BELAJAR KELOMPOK MATA DIKLAT PROGRAM STUDI KRIA TEKSTIL OLEH GURU SMK NEGERI 8 PADANG - YULHADI SAPUTRA, Drs. Ajusril S., Drs. Eswendi, M.Pd (Serupa The Journal of Art Education, 2014)
textile there are late in giving learners the value of the task, because there are some students who are late in collecting duties. The purpose of the study describes the learning outcomes assessment plan implemented kria textiles teacher of SMK Negeri 8 Padang, and the implementation of outcomes measurement study conducted kria textiles teacher of SMK Negeri 8 Padang. This research is a descriptive study using a quantitative approach, the whole population is kria textiles teacher who numbered 10 in SMK Negeri 8 Padang, all the sampled population. Results showed that learning outcomes assessment planning group eyes kria textile training courses by teachers of SMK Negeri 8 Padang including both categories (3.87). Preparation of the measuring instrument with quite good category (3.20). Implementation of the measurement of learning outcomes including good enough category (2.80). Scoring categories of learning outcomes is quite good (2.70).Keywords: Assessment , learning outcomes , textile kria